Les universités et la ville au moyen âge : cohabitation et tension - Gilli, Patrick; Verger, Jacques; Le Blévec, Daniel (Education and society in the Middle Ages and Renaissance ;, 2007)
The incorporation of universities into medieval cities produced specific difficulties for and benefits to urban communities. Ranging from Coimbra to Prague, the case studies collected in this volume examine the particular forms of contact between two institutions which marked the Middle Ages.